Answer:
r = 9
Step-by-step explanation:
3(r - 1) - 2(r + 3) = 0
First, use the distributive property.
3r - 3 -2r - 6 = 0
Now, isolate the variable "r" to one side by adding the opposite of the whole numbers to each side so it cancels it out on the left ide and adds it to the right.
3r - 3 -2r - 6 = 0
+3 +6 +3 +6
3r - 2r = 9
Subtract the r's.
r = 9
Now that we know r = 9, we can plug in 9 into the original (but distributed) expression for every time it uses the variable "r" to check our work.
3r - 3 -2r - 6 = 0
3(9) - 3 - 2(9) - 6 = 0
27 - 3 - 18 - 6 = 0
24 - 24 = 0
0 = 0
So, r = 9 is true.
Hope this helps! If you have any additional questions, please don't hesitate to ask me or your teacher to be sure you master the subject. Stay safe, and please mark brainliest!
Answer:
2
Step-by-step explanation:
its just the number in front of x
JK = JH + HK
JK = 82
JH = 22
So, HK = 82 - 22 = 60, or choice (C).

Given :


let's solve for f(x) × g(x) :



therefore, correct choice is : D
Answer:
we have only two or three acute angles in a triangle. so ima say at least 1
Step-by-step explanation: